2021
DOI: 10.1101/2021.05.06.442982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analyses of RNA-seq and genome-wide data point to enrichment of neuronal cell type subsets in neuropsychiatric disorders

Abstract: Neurologic, psychiatric and substance use disorders share a range of symptoms, which could be the result of shared genetic background. Many genetic loci have been identified for these disorders using genome-wide association studies, but conclusive evidence about cell types wherein these loci are active is lacking. We aimed to uncover implicated brain cell types in neuropsychiatric traits and to assess consistency in results across RNA datasets and methods. We therefore comprehensively employed cell-type enrich… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These observations fuel the concept of neuropsychiatry as a field in itself (Yudofsky and Hales, 2002). In contrast to the many shared characteristics between neurological and psychiatric disorders, recent findings point to a higher degree of genetic overlap between major psychiatric disorders in comparison to neurological disorders (Brainstorm Consortium et al, 2018;Olislagers et al, 2021). "Lumping and splitting" are common phenomena in medicine overall (Lüscher, 2019) and within psychiatry (Marquand et al, 2016).…”
Section: Cross-disorder Genetics In Neuropsychiatrymentioning
confidence: 86%
“…These observations fuel the concept of neuropsychiatry as a field in itself (Yudofsky and Hales, 2002). In contrast to the many shared characteristics between neurological and psychiatric disorders, recent findings point to a higher degree of genetic overlap between major psychiatric disorders in comparison to neurological disorders (Brainstorm Consortium et al, 2018;Olislagers et al, 2021). "Lumping and splitting" are common phenomena in medicine overall (Lüscher, 2019) and within psychiatry (Marquand et al, 2016).…”
Section: Cross-disorder Genetics In Neuropsychiatrymentioning
confidence: 86%
“…Our study identified additional sets of neurons (PVALB and LAMP5) as highly vulnerable cells to psychoactive drugs and show this vulnerability is specific to neurons from the TL. Integrating brain single cell with GWAS data, Olislagers et al 86 showed that neuronal cell subsets are consistently implicated in several psychiatric disorders. Our study confirms and extend these results, as we further refined the neuronal subtypes to the inhibitory sub-type (PVALB and SST) and again highlight their specificity to the TL.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating brain single cell with GWAS data, Olislagers et al . 86 showed that neuronal cell subsets are consistently implicated in several psychiatric disorders. Our study confirms and extend these results, as we further refined the neuronal subtypes to the inhibitory sub-type (PVALB and SST) and again highlight their specificity to the TL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation